12(b-3)=8(b-2)

Simple and best practice solution for 12(b-3)=8(b-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(b-3)=8(b-2) equation:


Simplifying
12(b + -3) = 8(b + -2)

Reorder the terms:
12(-3 + b) = 8(b + -2)
(-3 * 12 + b * 12) = 8(b + -2)
(-36 + 12b) = 8(b + -2)

Reorder the terms:
-36 + 12b = 8(-2 + b)
-36 + 12b = (-2 * 8 + b * 8)
-36 + 12b = (-16 + 8b)

Solving
-36 + 12b = -16 + 8b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-8b' to each side of the equation.
-36 + 12b + -8b = -16 + 8b + -8b

Combine like terms: 12b + -8b = 4b
-36 + 4b = -16 + 8b + -8b

Combine like terms: 8b + -8b = 0
-36 + 4b = -16 + 0
-36 + 4b = -16

Add '36' to each side of the equation.
-36 + 36 + 4b = -16 + 36

Combine like terms: -36 + 36 = 0
0 + 4b = -16 + 36
4b = -16 + 36

Combine like terms: -16 + 36 = 20
4b = 20

Divide each side by '4'.
b = 5

Simplifying
b = 5

See similar equations:

| 3(n+4)=5(n+1) | | 6x+32=13x-31 | | 8x=2x | | x^2-6x+9+3y=0 | | 4(k+2)=3(k+5) | | 10x+7=5x+22 | | (x-4)+5(x-3)=2(3x-5) | | 2x+6=42 | | 7y-9=3(y+5) | | 6(7-8x)=186 | | (2x+3)(5x-1)=0 | | 5(t-2)=t+10 | | 9p+6=3(p+8) | | 4b=6b+-19 | | 4(x+2)=3x+11 | | 3x^2+10+8=0 | | 3p^2-28=27p | | 4(n-1)=n+14 | | 4y^3-3=-12y^2+y | | 10+2z=20 | | -6+x=-10 | | 12t-1=14t-5 | | 8k+10=13k-5 | | 3v^2-7v-20= | | 3a=5a-18 | | 6(x+2)=3(x-5) | | 5x+37=14x-62 | | x^2+5x+18=9 | | 4x+7=x+16 | | 15r+22=97 | | 3(x-4)+5(x+3)=2(3x-5)-6 | | 6(2x-5)=42 |

Equations solver categories